Du PHENOTYPE - A REVIEW - Tayyab, Muhammad; Malik, Arif Rashid; Khan, Abdus Salam (Journal of Ayub Medical College Abbottabad, 2000)
Du is the phenotypic term used to denote a weakened expression of the D antigen. Du originally defined as those red cells reacting with anti-D only when a more sensitive indirect antiglobulin test was used. Du phenotype can arise from three different genetic situations, a) A person may inherit a gene coding for weakened quantitative expression of Du antigen, b) One gene may interact with another to modify and weaken the expression of the D antigen, c) A gene may not code for the total material that makes up the antigen. The frequency of D’1 antigen is relatively low less than 1%. D" is a poor immunogen, however, accelerated destruction of Du red cells can result if transfused to a person already making anti-D. Hence Du donor units are currently labelled as Rah positive. Du recipients are labelled as Rah negative. Newborn of Rah negative mother is tested for D & Du and Rh Ig is recommended for mothers of D positive or Du positive infants in order to prevent potential immunisation. The terms Du variant or partial D’; are recommended when there is both a qualitative and quantitative difference noted in the D antigen.